2012
DOI: 10.2478/v10298-012-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Brenneria Nigrifluens Strains in North of Iran (Margin of Caspian Sea)

Abstract: Genetic Diversity ofBrenneria NigrifluensStrains in North of Iran (Margin of Caspian Sea)Brenneria nigrifluens, the cause of shallow bark canker of Persian walnut trees (Juglans regiaL.), has become fairly widespread in Iran in recent years. It is regarded as a great threat to walnut production. To determine the diversity ofB. nigrifluensstrains, sixty strains of the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The main countries in which they have been reported are Iran (Yousefi et al, 2007;Jamalzade et al, 2012;Roshangar and Harighi, 2009), France, Spain (Loreti et al, 2008), Italy (Loreti et al, 2005;Pardatscher and Schweigkofler, 2009) and the United States (Wilson et al, 1957). (Yousefi et al, 2007;Jamalzade et al, 2012;Roshangar y Harighi, 2009), Francia, España (Loreti et al, 2008), Italia (Loreti et al, 2005;Pardatscher y Schweigkofler, 2009) y Estados Unidos (Wilson et al, 1957). En el Cuadro 1 se resumen reportes de Brenneria causante de cancro del nogal en distintas regiones del mundo, así como las técnicas utilizadas para la identificación de los patógenos.…”
Section: Distribution Of the Diseaseunclassified
“…The main countries in which they have been reported are Iran (Yousefi et al, 2007;Jamalzade et al, 2012;Roshangar and Harighi, 2009), France, Spain (Loreti et al, 2008), Italy (Loreti et al, 2005;Pardatscher and Schweigkofler, 2009) and the United States (Wilson et al, 1957). (Yousefi et al, 2007;Jamalzade et al, 2012;Roshangar y Harighi, 2009), Francia, España (Loreti et al, 2008), Italia (Loreti et al, 2005;Pardatscher y Schweigkofler, 2009) y Estados Unidos (Wilson et al, 1957). En el Cuadro 1 se resumen reportes de Brenneria causante de cancro del nogal en distintas regiones del mundo, así como las técnicas utilizadas para la identificación de los patógenos.…”
Section: Distribution Of the Diseaseunclassified
“…The walnut is one of the most invaluable plants that has wood, fruit, industrial, foreign exchange importance besides its other useful specifications and plays an important role in economic of the country. In countries wherein walnut is cultivated on widespread level, different diseases can be observed that introduce irreparable damages to the walnut trees (Jamalzade et al 2012).…”
Section: Introductionmentioning
confidence: 99%